Genetic diversity of bats coronaviruses in the Atlantic Forest hotspot biome, Brazil - Góes, Luiz Gustavo Bentim; Campos, Angélica Cristine de Almeida; Carvalho, Cristiano de [UNESP]; Ambar, Guilherme [UNESP]; Queiroz, Luzia Helena [UNESP]; Cruz-Neto, Ariovaldo Pereira [UNESP]; Munir, Muhammad; Durigon, Edison Luiz (Elsevier, 2016)
Bats are notorious reservoirs of genetically-diverse and high-profile pathogens, and are playing crucial roles in the emergence and re-emergence of viruses, both in human and in animals. In this report, we identified and characterized previously unknown and diverse genetic clusters of bat coronaviruses in the Atlantic Forest Biome, Brazil. These results highlight the virus richness of bats and their possible roles in the public health.